Urban Migrants in China - Zhou, Daming (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the background, migration, and settlement of new migrants in China. It also examines the status of their social networks, the role of urban society, social security, and future planning. Based on semi-structured interviews, the book analyzes these aspects of new urban migrants and argues that: - Intellectual migrants, with their strong educational background, are willing to engage in urbanization and have clear entry strategies. - Labor migrants find it is challenging for labor migrants to receive the same welfare as citizens and they are subject to significant segregation in urban societies due to existing policies and market economy conditions. - Operational migrants have stronger settlement and family-oriented tendencies compared to labor migrants.
Introduction -- Living Situation of Labor Migrants -- Living Situation of Intelligent Migrants -- Comparative Analysis among Labor Migrants, Intelligent Migrants and Business Migrants -- Migration and Settling of New Urban Migrants -- Social Network of New Urban Migrants -- Identity and Community Life of New Urban Migrants -- Adaptation and Integration of New Urban Migrants -- Social Mobility of New Urban Migrants -- Social Insurance of New Urban Migrants.
Keywords: Geography; Social structure; Equality; Sociology, Urban; Regional Geography; Social Structure; Urban Sociology